2017
DOI: 10.1093/sleep/zsx198
|View full text |Cite
|
Sign up to set email alerts
|

Informal Care and Sleep Disturbance Among Caregivers in Paid Work: Longitudinal Analyses From a Large Community-Based Swedish Cohort Study

Abstract: Study ObjectivesTo examine cross-sectionally and prospectively whether informal caregiving is related to sleep disturbance among caregivers in paid work.MethodsParticipants (N = 21604) in paid work from the Swedish Longitudinal Occupational Survey of Health. Sleeping problems were measured with a validated scale of sleep disturbance (Karolinska Sleep Questionnaire). Random-effects modeling was used to examine the cross-sectional association between informal caregiving (self-reports: none, up to 5 hours per wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 64 publications
2
18
0
1
Order By: Relevance
“…Null hypothesis 1 can therefore be rejected as co-resident care-givers had significantly higher odds of reporting problematic sleep after one year than those not providing care, independent of potential confounding variables. Studies using repeated measurements have found similar significant associations between care-giving and sleep over a period of seven days (Rowe et al, 2008) and two years (Sacco et al, 2018), though not among all studies (von Kaenel et al, 2012;Song et al, 2017). The present study found 27 per cent of co-resident care-givers suffered problematic sleep, in comparison to 24 per cent of non-care-givers (Table 2).…”
Section: Multivariate Analysessupporting
confidence: 66%
See 2 more Smart Citations
“…Null hypothesis 1 can therefore be rejected as co-resident care-givers had significantly higher odds of reporting problematic sleep after one year than those not providing care, independent of potential confounding variables. Studies using repeated measurements have found similar significant associations between care-giving and sleep over a period of seven days (Rowe et al, 2008) and two years (Sacco et al, 2018), though not among all studies (von Kaenel et al, 2012;Song et al, 2017). The present study found 27 per cent of co-resident care-givers suffered problematic sleep, in comparison to 24 per cent of non-care-givers (Table 2).…”
Section: Multivariate Analysessupporting
confidence: 66%
“…Transitions, and their influence on stress outcomes, is an important concept at the heart of the stress process (Pearlin, 2010). Previous research has found ceasing care-giving was associated with reduced sleep problems (Sacco et al, 2018), but von Kaenel et al (2012 found increased sleep disturbance after three months, where ceasing care-giving was as a result of spousal death. Our analyses found neither entering into care-giving nor ceasing care-giving had significantly different odds of reporting problematic sleep in the following year compared to non-care-givers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies with denser measurements of both exposures from work environment factors as well as insomnia symptoms are needed. Potential confounding factors not included in this study are factors in private life, such as taking care of a partner (Sacco, Leineweber, & Platts, ) or children (Estrela, Barker, Lantagne, & Gouin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on multimorbidity are crucial as it is an important risk concept associated with increased disability ( 8 , 9 ), poorer quality of life ( 10 ), and premature mortality ( 11 ). Caregivers are known to be at increased risk of stress ( 12 ), sleep problems ( 13 ), and unhealthy behavior such as smoking ( 14 ) and lack of physical activity ( 15 ), and these may increase risk for multimorbidity. Moreover, one previous U.S. study including 359 spousal caregivers and care recipients found that caregivers with multiple chronic conditions had greater emotional and physical difficulties than those without multiple chronic conditions ( 16 ), underlying the point that the presence of multiple chronic conditions may favor the onset of negative care-related outcomes (eg, poor physical health, subjective burden, low care-related quality of life).…”
mentioning
confidence: 99%